2015
DOI: 10.1371/journal.pone.0142704
|View full text |Cite
|
Sign up to set email alerts
|

Vorinostat Enhances Cytotoxicity of SN-38 and Temozolomide in Ewing Sarcoma Cells and Activates STAT3/AKT/MAPK Pathways

Abstract: Histone deacetylase inhibitors (HDACi) have been evaluated in patients with Ewing sarcoma (EWS) but demonstrated limited activity. To better understand the potential for HDACi in EWS, we evaluated the combination of the HDACi vorinostat, with DNA damaging agents SN-38 (the active metabolite of irinotecan and topoisomerase 1 inhibitor) plus the alkylating agent temozolomide (ST). Drugs were evaluated in sequential and simultaneous combinations in two EWS cell lines. Results demonstrate that cell viability, DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…Knockdown of EWS/FLI1 was also coupled to decreases in cyclin D1 and promotion of p53 expression [38, 39] which were observed after EGFR inhibition in our experiments. Thus, activities displayed by an EGFR inhibitor are consistent with other experimental agents that induce antiproliferative effects in ES associated with stimulation of p53 expression [40-42]. The combined actions of inhibiting protein kinase signaling and reducing cyclin D1 expression while promoting expression of p53 highlight the potential of EGFR inhibition to target both growth and cell cycle progression pathways, which are required for EWS/FLI1-induced malignant transformation [43].…”
Section: Discussionsupporting
confidence: 64%
“…Knockdown of EWS/FLI1 was also coupled to decreases in cyclin D1 and promotion of p53 expression [38, 39] which were observed after EGFR inhibition in our experiments. Thus, activities displayed by an EGFR inhibitor are consistent with other experimental agents that induce antiproliferative effects in ES associated with stimulation of p53 expression [40-42]. The combined actions of inhibiting protein kinase signaling and reducing cyclin D1 expression while promoting expression of p53 highlight the potential of EGFR inhibition to target both growth and cell cycle progression pathways, which are required for EWS/FLI1-induced malignant transformation [43].…”
Section: Discussionsupporting
confidence: 64%
“…During the cell cycle, the G2/ M checkpoint is a possible target for cancer therapy, and CDK/cyclin are critical and complex regulators of the G2/M phase [20]. Recent studies have demonstrated that various anticancer drugs induce G2/M arrest accompanied by downregulating the expression levels of AKT [21]. In our study, the results showed that cytisine treatment resulted in G2/M arrest and decreased expression of p-AKT, CDK1/2, and cyclin B1, and increased the expression of p27 and p21, suggesting that the AKT signalling pathway may be the molecular mechanism through which cytisine induced G2/M phase arrest (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the research direction of cancer has been transferred into protein molecular level. Aberrant protein glycosylation is known to be associated with the development of cancers [ 20 - 23 ]. FUTs are key enzymes have been implicated in differentiation, development and malignancy of human cancer through the fucosylation of proteins [ 15 ].…”
Section: Discussionmentioning
confidence: 99%